2019
DOI: 10.1042/cs20180562
|View full text |Cite
|
Sign up to set email alerts
|

Sodium 4-phenylbutyrate treatment protects against renal injury in NZBWF1 mice

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease predominantly affecting women and often leading to lupus nephritis and kidney damage. Endoplasmic reticulum (ER) stress has been implicated in several forms of kidney disease, but whether ER stress contributes to renal injury in SLE is unknown. To investigate this, a small molecule chaperone, sodium 4-phenylbutyrate (4-PBA), was administered to the New Zealand Black x New Zealand White F1 hybrid (NZBWF1) mouse model of SLE. In a prevention study, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…To determine whether the mitochondrial dysfunction observed in 65-79*LE-treated macrophages is secondary to ER stress, we used sodium 4-phenylbutyrate (4-PBA), a chemical chaperone that inhibits protein misfolding, thereby inhibiting ER stress 44 . Relevant to the present study, 4-PBA has been shown to prevent SLE manifestations in experimental lupus models 45,46 . As expected, 4-PBA inhibited 65-79*LE-activated ER stress and proteasomal degradation (Fig.…”
Section: Resultssupporting
confidence: 66%
“…To determine whether the mitochondrial dysfunction observed in 65-79*LE-treated macrophages is secondary to ER stress, we used sodium 4-phenylbutyrate (4-PBA), a chemical chaperone that inhibits protein misfolding, thereby inhibiting ER stress 44 . Relevant to the present study, 4-PBA has been shown to prevent SLE manifestations in experimental lupus models 45,46 . As expected, 4-PBA inhibited 65-79*LE-activated ER stress and proteasomal degradation (Fig.…”
Section: Resultssupporting
confidence: 66%
“…In a resiquimod-induced SLE mouse model, treatment with 4-PBA significantly mitigated ER stress signaling, attenuated splenomegaly—a common clinical manifestation in SLE -, reduced levels of TNF-α and anti-dsDNA, significantly ameliorated LN, reduced proportion of activated T and B lymphocytes and improved Treg-dependent immune suppression [ 39 ]. In another study involving a mouse model of SLE, treatment with 4-PBA increased renal expression of GRP78 and also mitigated renal injury development and progression [ 40 ]. These findings implicate noxious protein accumulation as a central component in the pathogenesis of SLE.…”
Section: The Unfolded Protein Responsementioning
confidence: 99%
“…In GSE94717, the concentration of microR-380-3p is up-regulated in patients with septic AKI through analysis by GEO2R program. As an autoimmune disease, systemic lupus erythematosus is a reason for kidney injury (Bonnemaison et al 2019). In lupus nephritis patients with systemic lupus erythematosus, the concentration of microR-380-3p is increased and its increased levels may serve as a risk predictor in diagnosing patients with systemic lupus erythematosus companies with renal injury (Navarro-Quiroz et al 2016).…”
Section: Discussionmentioning
confidence: 99%